Endurance exercise training-attenuated diabetic kidney disease with muscle weakness in spontaneously diabetic Torii fatty rats. - Hitoshi Kotake; Shohei Yamada; Yuji Ogura; Shiika Watanabe; Kazuho Inoue; Daisuke Ichikawa; Takeshi Sugaya; Keiichi Ohata; Yasunori Natsuki; Seiko Hoshino; Minoru Watanabe; Kenjiro Kimura; et al. (Karger Publishers, 2021)
Abstract Background The aim of this study was to evaluate protective effects of endurance exercise training against diabetic kidney disease (DKD) with muscle weakness by using male spontaneously diabetic Torii (SDT) fatty rats as type 2 diabetic animal models with obesity, hypertension, and hyperlipidemia. Methods Eight-week-old SDT fatty rats (n = 12) and Sprague-Dawley (SD) rats (n = 10) were randomly divided into exercise (Ex; SDT-Ex: n = 6, SD-Ex: n = 5) and sedentary groups (SDT-Cont: n = 6, SD-Cont: n = 5), respectively. Each group underwent regular treadmill exercise four times a week from ages 8 to 16 weeks. Results The exercise attenuated hypertension and hyperlipidemia and prevented increases in renal parameter levels without affecting blood glucose levels. In the SDT fatty rats, it prevented induction of renal morphological abnormalities in the interstitium of the superficial and intermediate layers of the cortex. Downregulated expression of endothelial nitric oxide synthase in the glomerulus of the SDT fatty rats was significantly upregulated by the exercise. The exercise upregulated the renal expressions of both medium-chain acyl-CoA dehydrogenase and peroxisome proliferator-activated receptor γ coactivator-1α related to fatty acid metabolism. It increased muscle strength and both muscle weight and cross-sectional area of type IIb muscle fibers in the extensor digitorum longus muscle in the SDT fatty rats. Conclusion Endurance exercise training in type 2 diabetes ameliorates DKD by improving endothelial abnormality and enhancing fatty acid metabolism in addition to attenuated hypertension, hyperlipidemia, and muscle weakness independently of blood glucose levels.